Pembelajaran Sejarah SMA Negeri 1 Berau Berbasis Situs Peninggalan Belanda di Teluk Bayur - Elvinas Septian Indiani; Jamil Jamil; Sainal A (Amarthapura: Historical Studies Journal, 2022)
The use of the Dutch heritage site in Teluk Bayur as a learning resource is intended to improve history learning at SMAN 1 Berau and also to enrich history learning resources. The purpose of this study was to describe the historical learning process at SMAN 1 Berau by utilizing the Dutch heritage site in Teluk Bayur and the teacher’s obstacles in the process of utilizing the Dutch heritage site as a learning resource. The type of research used ia a qualitative approach. The result of this study show how the learning process at SMAN 1 Berau runs according to the existing curriculum and the use of Dutch heritage sites as a learning resource makes students have a high enthusiasm for learning, and students can add social attitudes toward historical sites in the environment.